Serodiagnosis of Helicobacter hepaticus infection in mice by an enzyme-linked immunosorbent assay. - Livingston, R S (1997)
Helicobacter hepaticus is a newly recognized bacterium associated with chronic active hepatitis, hepatic carcinoma, and inflammatory bowel disease in mice. Currently, fecal or tissue PCR, fecal culture, or histologic examination of silver-stained liver sections is used to diagnose H. hepaticus infection. In this report, we describe an enzyme-linked immunosorbent assay (ELISA) for serodiagnosis of H. hepaticus infection in mice with a membrane digest preparation of H. hepaticus as the antigen. Sera from mice positive for H. hepaticus by PCR or histologic examination (n = 88), positive for Helicobacter bilis by PCR (n = 13), positive for other helicobacters (not identifiable to species level) by PCR (n = 25), or negative for all Helicobacter species by PCR (n = 162) were used to evaluate the ELISA. Results indicated that ELISA provided 93.2% sensitivity, 94% specificity, 87.2% positive predictive value, and 96.9% negative predictive value. Cross-reactive antibodies were detected in some mice infected with helicobacters not identifiable to species level. To further define ELISA sensitivity and specificity, groups of 10 C57BL/6 mice were inoculated per os with H. hepaticus, Helicobacter muridarum, or H. bilis. Sera were collected and examined by the ELISA. H. hepaticus-infected mice seroconverted by 2 weeks and maintained ELISA reactivity throughout the 18-week study, while mice infected with H. muridarum and H. bilis were negative by ELISA. These results indicate that this reported ELISA is highly sensitive and specific for the serodiagnosis of H. hepaticus infection in mice.